Experimental Study of District Heating Substations in a Hardware-in-the-Loop Test Rig - Anna Vannahme; Jonas Busch; Mathias Ehrenwirth; Tobias Schrag (Resources, 2023)
This study compares two district heating substation systems for implementation in rural district heating networks with non-retrofitted single- and two-family houses. The aim is to determine which system has the potential to provide lower return temperatures and/or lower power peak demand. A hardware-in-the-loop-test rig was utilized to measure the two district heating substations under real operation conditions. This experimental study demonstrates that load balancing of the district heating network is attainable with the district heating substation with storage. This is especially advantageous when there is a high demand for domestic hot water. Overall, both systems yield comparable return temperatures.